LEGAL ANALYSIS OF THE ROLE OF BPJS KESEHATAN IN THE DISPUTE OVER THE FINANCING OF MEDICAL SERVICES IN HOSPITALS - Zainuddin; Marice Simarmata (Yayasan Multidimensi Kreatif, 2025)
The financing system for medical services in Indonesia, which is managed by the Social Security Administration Agency (BPJS) Kesehatan, is one of the important aspects in ensuring access to health for the community. However, the practice of financing often causes disputes between BPJS and hospitals regarding claims for medical service costs that are considered inappropriate. This dispute raises legal and administrative problems that have the potential to disrupt the smooth running of health services and patient rights. Therefore, an in-depth analysis of the legal role of BPJS Kesehatan in resolving the financing dispute is needed. This research aims to examine the legal role of BPJS Kesehatan in handling medical service financing disputes in hospitals and identify legal obstacles that arise in the dispute resolution process. In addition, this research also aims to provide recommendations for improving regulations and dispute resolution procedures to be more effective, fair, and transparent. The research method used is a normative qualitative approach with data collection techniques through the study of laws and regulations documents, cooperation contracts between BPJS and hospitals, as well as interviews with related parties such as BPJS managers, hospital management, and health law experts. The data were analyzed using normative and sociological juridical methods to obtain a comprehensive picture of legal aspects and their implementation. The results of the study revealed that BPJS's legal role in medical service financing disputes is still experiencing obstacles, especially due to the lack of detailed technical rules regarding claim procedures and dispute resolution mechanisms. This lack of clarity triggers tension between BPJS and hospitals, as well as has a negative impact on medical services. Therefore, strengthening regulations, transparency of claims procedures, and increasing the capacity of human resources in legal aspects are very necessary to optimize the function of BPJS in resolving financing disputes. The conclusion of the study states that the legal role of BPJS Kesehatan in medical service financing disputes needs to be improved through regulatory revision and the implementation of a more effective and accountable settlement mechanism. Recommendations were given for BPJS and hospitals to strengthen coordination and communication, as well as build a responsive dispute resolution system to maintain the quality of health services and public trust.